Analisis Penerapan GCG Dalam Perspektif Syariat Islam pada Bank Muamalat Indonesia - Supardi Supardi; Asyaadatun Nazila Selayan; Rahmatul Fadilah; Juliana Nasution (LPPM IAI Nasional Laa Roiba Bogor, 2023)
Indonesia is a country where the majority of the population is Muslim where it is very important to know the principles of GCG Islamically in the implementation of business. The application of the principles of Good Corporate Governance (GCG) in Islamic banks is very important. This is because Islamic banks as intermediary institutions are collecting funds from the public and distributing them to people who need them. Thus, efforts to maintain public trust in banking are a very important part to do. One way to maintain public trust is to apply the principles contained in Good Corporate Governance. This study aims to determine the implementation of GCG in BMI, and whether it is in accordance with Islamic law. This type of research uses descriptive qualitative research. The results of this study indicate that the application of the principles of Good Corporate Governance (GCG) at Bank Muamalat Indonesia, namely accountability, professionalism, transparency, responsibility, and fairness (equity) has been carried out properly in accordance with applicable guidelines and regulations. Keywords: Principles of Good Corporate Governance, Bank Muamalat, Islamic Sharia.